Morphology in the Era of Large Surveys - Lintott, C; Masters, K; Simmons, B; Bamford, S; Kaviraj, S (2013)
The study of galaxies has changed dramatically over the past few decades with the advent of large-scale astronomical surveys. These large collaborative efforts have made available high-quality imaging and spectroscopy of hundreds of thousands of systems, providing a body of observations which has significantly enhanced our understanding not only of cosmology and large-scale structure in the universe but also of the astrophysics of galaxy formation and evolution. Throughout these changes, one thing that has remained constant is the role of galaxy morphology as a clue to understanding galaxies. But obtaining morphologies for large numbers of galaxies is challenging; this topic, "Morphology in the era of large surveys", was the subject of a recent discussion meeting at the Royal Astronomical Society, and this "Astronomy and Geophysics" article is a report on that meeting.